1986
DOI: 10.1104/pp.80.4.1020
|View full text |Cite
|
Sign up to set email alerts
|

A Semidian Rhythm in the Flowering Response of Pharbitis nil to Far-Red Light

Abstract: ABSTRACT?Evidence is presented of an endogenous rhythm in flowering response to far-red (FR) irradiation, with a period of about 12 h (hence semidian rhythm), which persists through at least three cycles in constant conditions of continuous light at 27°C and has a marked influence on the flowering response in Pharbitis nil to a subsequent inductive dark period. The phase of the rhythm is not influenced by real time nor by the time from imbibition or from the beginning of the light period. Rather, it is fed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The results of a third experiment, in which FR pretreatments were given either 2, 8, 15 or 22 h before a dark period of 13,5 h are shown in Fig, 2b, The close similarity of the two FR -2 h curves in Fig, 2a the two FR -8 h curves, indicates how highly reproducible these responses are. FR pretreatments at -2 and -15 h promote flowering whereas those at -8 and -22 h are inhibitory as shown by Heide et al (1986) and . The data in Fig.…”
Section: Effect Of Duration and Time Of Exposure To Red Interuptions mentioning
confidence: 85%
See 2 more Smart Citations
“…The results of a third experiment, in which FR pretreatments were given either 2, 8, 15 or 22 h before a dark period of 13,5 h are shown in Fig, 2b, The close similarity of the two FR -2 h curves in Fig, 2a the two FR -8 h curves, indicates how highly reproducible these responses are. FR pretreatments at -2 and -15 h promote flowering whereas those at -8 and -22 h are inhibitory as shown by Heide et al (1986) and . The data in Fig.…”
Section: Effect Of Duration and Time Of Exposure To Red Interuptions mentioning
confidence: 85%
“…The fact that the rhythm was less advanced after FR -15 h than after FR -2 h could have been due to a small shift in the penultimate semidian peak in this experiment (cf. Heide et al 1986; Fig. 3).…”
Section: Effect Of Duration and Time Of Exposure To Red Interuptions mentioning
confidence: 94%
See 1 more Smart Citation
“…The exposure of plants to white light of low intensity resulted in lightlabile phytochrome degradation. This model was described and used previously (Heide et al, 1986;Kopcewicz, 1994, 1995;Łukasiewicz-Rutkowska et al, 1997;Kulikowska-Gulewska and Kopcewicz, 2002;Maciejewska et al, 2004). P. nil grown in these special photoperiodic conditions formed four axillary flower buds and one terminal flower bud per plant.…”
Section: Article In Pressmentioning
confidence: 99%
“…The complicated nature of the timing mechanism is illustrated by the short-day plant, Pharbitis nil, for which endogenous rhythms are well characterized Hamner, 1964, 1965;Spector and Paraska, 1973;Evans et al, 1986;Heide et al, 1986Heide et al, , 1988Lumsden et al, 1982;VincePrue, 1975). For this short-day plant, physiological experiments have shown that the timing of the CNL and response to NB is controlled mainly by an endogenous rhythm initiated or reset at the onset of the main light period.…”
Section: Physiological Characterization Of Flowering and The Photorecmentioning
confidence: 99%